Investigations on optical properties of ZnO decorated graphene oxide (ZnO@GO) and reduced graphene oxide (ZnO@r-GO) - Kumar, Pushpendra; Som, Sudipta; Pandey, Mukesh K.; Das, Subrata; Chanda, Anupama; Singh, Jai (Journal of Alloys and Compounds, 2018)
The present investigation is based on the production of reduced graphene oxide (r-GO) from the graphene oxide using Hummer's (GO) and improved Hummer's methods (IGO) at elaborated conditions, named as GO and IGO, respectively hereafter. In contrast to previously known techniques, the presented process does not generate toxic gas. Meanwhile, the reduction temperature can be easily controlled. This approach provides a more significant amount of hydrophilic oxidized graphene as compared to GO and IGO with the use of additional KMnO4. Thus synthesized IGO was used to produce r-GO by thermal treatment. The morphological characteristics show that the obtained samples have a wrinkled paper-like morphology with severely folded lines. However, r-GO has double layers and multilayer at the edges. All the products (GO, IGO, and r-GO) have been decorated with ZnO nanoparticles (NPs). The XRD patterns of ZnO@GO composites have confirmed the characteristic peaks of wurtzite ZnO indicating the formation of ZnO nanoparticles onto the surface of graphene. The microscopic studies confirm the random growth/decoration of ZnO NPs on the surface of GO/IGO/r-GO sheets. However, in IGO and r-GO, loading/growth of ZnO NPs are less as compared to ZnO@GO. Overall structural studies indicate the oxidation of graphite and reduction of graphene oxide into r-GO sheets and ZnO decoration. Upon UV excitations, a bright blue emission has been exhibited by the GO that originates from geminate recombination of localized e-h pairs in sp(2) clusters those primarily act as the luminescent centers. The noteworthy enhancement in the emission intensities after the incorporation of ZnO nanoparticles on the surface of GO is observed. The improved synthesis method and low-temperature reduction technique of GO may be essential for the large-scale production of r-GO as well as the construction of devices composed of ZnO@GO/IGO/r-GO. (C) 2018 Elsevier B.V. All rights reserved.